USAID Assistance to Economic Development of Bosnia and Herzegovina: Overview of Major Initiatives in Selected Sectors - Avdić Marić, Aida; Sivac, Amina; Avdić, Boris (European Journal of Geography, 2026)
Bosnia and Herzegovina, a Southeast European country and a European Union (EU) candidate state, is characterized by complex social, political and economic structures that influence its development trajectory. As a post-transition economy, it faces persistent structural challenges, including low economic growth and institutional fragmentation. The United States Agency for International Development (has been an important factor in supporting development through long-term programs, yet recent changes in the status of its operations have raised questions about the sustainability of its interventions and future economic dynamics. This paper examines the spatial distribution of selected USAID-funded economic projects in Bosnia and Herzegovina, focusing on diaspora investments, agriculture, tourism and energy policy. By analyzing program documentation and examining the spatial distribution of municipal-level participation, the study provides insights into the economic and geographic impact of USAID selected initiatives. The findings indicate an uneven territorial impact, with more frequent participation in municipalities with stronger institutional and economic capacity and more limited coverage in peripheral and structurally weaker areas. While the analyzed initiatives contributed to sectoral development and capacity-building, their uneven spatial concentration suggests potential territorial vulnerabilities over time. In this context, USAID’s engagement in Bosnia and Herzegovina has been economically, institutionally and geopolitically significant. Highlights: Recent USAID activities in Bosnia and Herzegovina had economic impact with spatial disparities. Since 2020, key programs focus on agriculture, energy, tourism and diaspora investment. Termination of USAID programs threatens many projects vital to local communities.